Knowledge and Practice Regarding Prevention and Management of Rabies among Allopathic and Ayush Private Practitioners in Urban Maharashtra: A Comparison Study - Kotnis, Shubhalaxmi D; Deshmukh, Sangita C (National Journal of Community Medicine, 2017)
Introduction: Rabies is endemic in many Asian and African Countries, including India. Correct management of animal bite cases by all practicing physicians will help India to be Rabies free country. Method: A cross sectional survey using convenient sampling with snow ball method. The study period was from 1st July2011 to 31st October. The registered private practitioners from various regions in the city were selected for study. Their permission obtained orally. Data collection was done using pre-tested questionnaire by interview method. Results: 97% Allopathic doctors and 94.73% AYUSH doctors had correct knowledge about the agent of Rabies. Only to 68.54% of Allopathic and 43.42% of AYUSH doctors knew modes of transmission. Important clinical symptoms were told by66.93% of Allopathic and 35.52% of AYUSH doctors. 63.7%of allopathic, 39.47% AYUSH doctors where having knowledge about available vaccines. Only 49.19% allopathic and 11.84% AYUSH doctors told Vaccination schedule 71.77% allopathic and 22.36% AYUSH doctors knew about wound washing with soap and water for 15 minutes.